Application of density tracers in a dense medium circuit: A case study. (1st June 2018) - Izerdem, D.; Orhan, E.C.; Ozcan, O.; Alpay, E.
Highlights: Density tracers are used to evaluate the performance of DM drums and cyclones. The separation efficiency limitations of dense medium drums are highlighted. The extent of retention in dense medium cyclones were determined. Density tracers enable quick and reliable performance prediction in DMS circuits. Abstract: Density tracers are often used to identify the separation efficiency of mineral processing equipment and the overall plant performance in several mineral and coal applications. In a 700 t/h coal washing plant in Turkey, comprising dense medium drums and dense medium cyclones, a plant audit was conducted using density tracers. In this study, the data obtained from the dense medium cyclone and drum circuits during the plant survey are presented. Besides the detailed separation behavior of the particles in the drums and cyclones, some variables affecting the performance such as particle retention, separation cut-point and separation efficiency are also discussed. Based on the efficiency data from the plant audit, the mass balance of the plant was obtained using an in-house-developed coal washing plant simulator (LAVE) by using the size-by-size washability data of the run-of-mine (ROM) coal and the plant control room data.